Prevalence and Pathological Lesions of Dermatophytosis in Cats (Felis catus) at the Animal Health Center in Cimahi: August-September 2023 - Fauziyah, Sri Nur Farah; Dewi, Intan Mauli Warma; Khairani, Shafia (Journal of Parasite Science, 2025)
Dermatophytosis is a zoonotic fungal infection affecting the superficial skin layer. characterized by circular lesions commonly referred to as "ringworm." This condition has been recorded as the most frequently occurring ailment at the Animal Health Center in Cimahi. This study aims to determine the prevalence and characteristics of dermatophytosis lesions in cats at the Animal Health Center in Cimahi during the period of August-September 2023. Samples were collected based on physical examinations and supporting diagnostics. such as Wood's lamp inspection. on animals suspected of having dermatophytosis. The results revealed that the prevalence of dermatophytosis in cats during the specified period was 10.5%. with 91 cases out of 864 patients. The most common lesions observed included epidermal collars with scales. crusts. erythema. hyperpigmentation. and alopecia. totaling 613 lesions from 91 patients. The highest number of lesions was found in the dorsal body region. with a total of 115 lesions. Predisposing factors such as age. sex. and breed indicated that dermatophytosis was most prevalent in cats aged less than 6 months (38 cats. 41.7%). female cats (46 cats. 50.5%). and domestic breed cats (40 cats. 43.9%). This study contributes valuable epidemiological data on dermatophytosis in animals in Indonesia.